Designing guidelines for responsible and environmentally sustainable ICT supplier selection : Increasing green ICT awareness in the case organization - Mustonen, Martta (My University, 2024)
ICT is seen as both a solution and a cause for environmental challenges. When ICT reduces emissions from other sectors, the sector's own emissions and carbon footprint will increase. A significant proportion of the sector's emissions come from ICT equipment, representing 47-54% of total greenhouse gases in the ICT sector. The responsibility of these emissions lies not only with the manufacturers of the equipment, but also with the organizations representing their large group of users. The identification of the adverse impacts of ICT has led to increased demands for organizations to act responsibly and in an environmentally sustainable manner, and to adopt green ICT levers. Efforts have been made to promote ICT's environmental sustainability through changes in sourcing and supplier selection criteria. It is estimated that by 2026, 70% of technology sourcing leaders will have performance objectives aligned to environmental sustainability and 75% of the organizations will increase business with ICT suppliers that provide sustainability targets and timelines. The study aims to design guidelines for responsible and environmentally sustainable ICT equipment supplier selection. The study is conducted for a case organization that represents an ICT support organization of a Finnish engineering company. The study problem arises from the case organization’s need to increase awareness of the adverse environmental impacts of ICT and understand their role in decreasing them. Two research questions have been set for the study: what are the aspects that should be considered in supplier selection to promote environmental sustainability and reduce the environmental burden associated with the sourced ICT equipment, and how does incorporating environmental sustainability in the supplier selection contribute to sustainability efforts in the case organization. The study is an action design research. To answer the research questions, the first step is to establish a theoretical basis for the topic, after which the empirical part of the study is carried out through workshops. A total of three workshops are held during the design development process, in which the researcher works together and collects input from the professionals from the case organization to design the guidelines to adopt greener supplier selection practices. As a result of the study, the case organization has guidelines to promote responsible and environmentally sustainable ICT equipment supplier selection. The guidelines support the case organization’s journey towards greener ICT operation, the implementation of an environmental perspective into sourcing processes, cooperation with environmentally responsible suppliers, the selection of environmentally friendly equipment, and adoption of circular economy principles. Further research is proposed to implement and test the guidelines and to continue the development of green ICT adoption in other areas of ICT.

Tieto-ja viestintätekniikka (ICT) nähdään sekä ratkaisuna että ympäristöhaasteiden aiheuttajana. ICT:n vähentäessä muiden alojen päästöjä, alan omat päästöt ja hiilijalanjälki kasvavat. Merkittävä osa alan päästöistä on peräisin ICT-laitteista, joiden osuus on 47-54 prosenttia koko ICT-alan kasvihuonekaasujen kokonaismäärästä. Päästöt ovat paitsi laitteiden valmistajien vastuulla, myös niiden suurta käyttäjäjoukkoa edustavien organisaatioiden vastuulla. ICT:n haitallisten vaikutusten tunnistaminen on johtanut siihen, että organisaatioita vaaditaan entistä enemmän toimimaan vastuullisesti ja ympäristön kannalta kestävällä tavalla sekä omaksumaan keinoja vihreän ICT:n toteuttamiseksi. ICT:n ympäristökestävyyttä on pyritty edistämään hankinnan muutoksilla ja toimittajan valintakriteereiden avulla. On arvioitu, että vuoteen 2026 mennessä 70 prosentilla teknologiahankinnan johtajista on tulostavoitteet linjassa ympäristön kestävän kehityksen tavoitteiden kanssa ja 75 prosentilla organisaatioista on enemmän liiketoimintaa ICT-toimittajien kanssa, jotka pystyvät esittämään todistetusti kestävyystavoitteita ja aikatauluja. Tutkimuksen tavoitteena on suunnitella suuntaviivat vastuulliselle ja ympäristön kannalta kestävälle ICT-laitteiden toimittajavalinnalle. Tutkimus tehdään kohdeorganisaatiolle, joka edustaa suomalaisen konepajayrityksen ICT-tukiorganisaatiota. Tutkimusongelma syntyy tapausorganisaation tarpeesta lisätä tietoisuutta ICT:n haitallisista ympäristövaikutuksista ja ymmärtää heidän roolinsa niiden vähentämisessä. Tutkimukselle on asetettu kaksi tutkimuskysymystä: mitkä ovat näkökohdat, jotka olisi otettava huomioon toimittajavalinnoissa ympäristökestävyyden edistämiseksi ja hankittujen ICT-laitteiden ympäristökuorman vähentämiseksi, ja miten ympäristökestävyyden sisällyttäminen toimittajavalintaan edistää kestävyyspyrkimyksiä tapausorganisaatiossa. Tutkimus on toiminnan suunnittelututkimus. Tutkimuskysymyksiin vastaamiseksi ensimmäinen vaihe on teoreettisen perustan luominen aiheelle, jonka jälkeen tutkimuksen empiirinen osa toteutetaan työpajojen kautta. Suunnitteluprosessin aikana järjestetään yhteensä kolme työpajaa, joissa tutkija yhdessä kohdeorganisaation ammattilaisten kanssa suunnittelee ja kehittää suuntaviivoja vihreämpään toimittajavalintaan. Tutkimuksen tuloksena kohdeorganisaatiolla on suuntaviivat vastuullisen ja ympäristön kannalta kestävän ICT-laitteiden toimittajavalinnan toteuttamiseksi. Suuntaviivat tukevat kohdeorganisaation siirtymää kohti vihreämpää ICT-toimintaa, ympäristönäkökulman sisällyttämistä hankintaprosesseihin, ohjaavat yhteistyöhön ympäristövastuullisesti toimivien toimittajien kanssa, ympäristöystävällisten laitteiden valintaa ja kiertotalouden periaatteiden omaksumista. Jatkotutkimukseksi ehdotetaan suuntaviivojen implementointia ja testausta, sekä green ICT:n omaksumista muilla ICT:n osa-alueilla.
Keywords: information and communications technology; environmental responsibility; sustainable development; suppliers; guidelines; circular economy; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Tietojärjestelmätieteen maisteriohjelma|en=Master’s Programme in Information Systems|